(untitled) (REMUNOM, 2025)
This article aimed to describe the main energy products from elephant grass cultivation. Data collection was carried out through a survey of scientific productions, whose bibliographic references were based on books, articles, Scopus, Scielo, course completion papers, master’s and doctoral theses. The scientific papers were pre-selected and those considered most relevant were stored for better reading and understanding. Elephant grass has proven to be attractive to the energy market in different contexts, such as in the production of thermal energy, solid biofuels (pellets and briquettes) and even cellulosic ethanol. The use of elephant grass for the production of renewable energy biomass, aiming at its transformation into charcoal and dry matter for use in boilers, can significantly increase the area cultivated with this species. The juice remaining from the grinding of elephant grass has a high proportion of biomass, becoming an important raw material for the production of biogas through the anaerobic biodigestion process. Because it is a renewable energy source, does not compete with agricultural production for food, is widely available and has a low cost, elephant grass is an ideal plant biomass for the production of 2G ethanol. It is concluded that the production of bioenergy using elephant grass is one of the most promising alternatives for replacing energy from fossil fuels, bringing benefits to the environment by reducing greenhouse gas emissions.